Avaliação dos efeitos inseticida e repelência sobre Lutzomyia longipalpis em cães tratados permetrina 65% ou com a coleira impregnada com deltametrina 4% - Fernanda dos Santos Alves (2014)
Canine visceral leishmaniasis, a zoonosis of major importance in countries in South America, Europe and Asia, is an animal disease overshadowed by the fact that dogs are the main urban reservoirs. Attempts to control are aimed at reducing the risk of human infection rather than for dog's protection from a invariably fatal disease. Dog culling, as well as ethically unacceptable, did not produce reduction in the incidence of the human disease for several reasons, including failures in diagnosing, culling and the replacement by other susceptible animals. A viable method for the protection of dogs are the products with repellent and insecticide effects. Among the options are the 65 % permethrin pour on and 4 % deltamethrin-impregnated collar, both synthetic pyrethroids that are able to repel and kill the maim vector in Brazil, the Lutzomyia longipalpis. In order to verify the effectiveness of these products to provide protection to dogs through two main effects, the repellent and insecticide , permethrin 65 % and deltamethrin-impregnated collar were evaluated by exposing dogs treated with one of them or both to sandflies obtained a closed colony, which were later classified as alive or dead, and in males and in not engorged or engorged females. It was realized by comparing the 65% permethrin with deltamethrin-impregnatedcollar that the insecticidal effect was better in the group that used the collar (2%) than in group treated only with permethrin (1%). The opposite was observed in the repellency effect when permethrin showed better results (40%) than the deltamethrin impregnated collar (33%), with statistical difference. Comparing the bathed group to the one that was not bathed during the research at 21 days, the insecticidal effect was more significant in group that was not bathed(9 % ) compared to the bathed group (7%). At 60 days, the group undergoing baths showed better results compared to without bath (51% and 2%, respectively) . In other moments, no significant differences were observed. As for the repellency effect was noticed statistically significant difference only at 7 days and at 21 days, when the group with bath yielded better results (49% and 56% , respectively) difference. Regarding the ability of the deltamethrin-impregnated collar in causing the death of engorged, at 7 and 21 days, the group that was not bathed showed higher percentage of females alive and engorged (16% and 10% , respectively). Permethrin 65 % demonstrated increased efficiency in insecticidal effect, with statistically significant difference between the time that the dogs did not use the product (3,6% ) and after 60 days (17,1%) and between the initial time (3,6%) and at 90 days (20,8%). As for repellency, there were significant statistical difference only between the initial moment (29,1%) and after 60 days (37 %) compared. The combination of permethrin and the deltamethrin-impregnated collaer did not have a statistical difference.